Attitudes toward innovative mental health treatment approaches in Germany: E-mental health and home treatment - Lincke, Lena; Ulbrich, Lisa; Reis, Olaf; Wandinger, Elisa; Brähler, Elmar; Dück, Alexander; Kölch, Michael (Frontiers in Psychiatry, 2022)
E-mental health and home treatment are treatment approaches that have proven to be effective, but are only slowly implemented in the German health care system. This paper explores the attitudes toward these innovative treatment approaches. Data was collected in two large, non-clinical samples representative of the German population in spring 2020 (N = 2503) and winter 2020/2021 (N = 2519). Statistical associations between variables were examined using two-tailed tests. Binary and multinomial logistic regressions were performed to predict attitudes towards online-based treatment concepts and home treatment approaches. Only few (<20%) people preferred online-based treatment approaches, while a larger proportion (~50%) could imagine being treated at home. Overall, younger subjects were more open to online-therapy approaches, while people with lower education preferred more often a traditional therapy setting. Acceptance of online-therapy did not raise significantly during the first months of the COVID-19 pandemic. When different online-based treatment options were available, the probability of accepting home treatment significantly increased with increasing levels of therapeutic support. Further promotion of acceptance for online-therapy and home treatment seems to be necessary. In the future, more information on innovative treatment approaches should be actively provided.